Ischaemic heart disease mortality and years of work in trucking industry workers. Issue 8 (19th September 2012) - Hart, Jaime E; Garshick, Eric; Smith, Thomas J; Davis, Mary E; Laden, Francine
Abstract : Objectives: Evidence from general population-based studies and occupational cohorts has identified air pollution from mobile sources as a risk factor for cardiovascular disease. In a cohort of US trucking industry workers, with regular exposure to vehicle exhaust, the authors previously observed elevated standardised mortality ratios for ischaemic heart disease (IHD) compared with members of the general US population. Therefore, the authors examined the association of increasing years of work in jobs with vehicle exhaust exposure and IHD mortality within the cohort. Methods: The authors calculated years of work in eight job groups for 30 758 workers using work records from four nationwide companies. Proportional hazard regression was used to examine relationships between IHD mortality, 1985–2000, and employment duration in each job group. Results: HRs for at least 1 year of work in each job were elevated for dockworkers, long haul drivers, pick-up and delivery drivers, combination workers, hostlers, and shop workers. There was a suggestion of an increased risk of IHD mortality with increasing years of work as a long haul driver, pick-up and delivery driver, combination worker, and dockworker. Conclusion: These results suggest an elevated risk of IHD mortality in workers with a previous history of regular exposure to vehicle exhaust.